Indentured Muslims in the diaspora : identity and belonging of minority groups in plural societies - Legacy of Slavery and Indentured Labour: Past, Present, and Future (Conference) (2013 : Paramaribo, Suriname); Hassankhan, Maurits S.; Vahed, Goolam H., 1961-; Roopnarine, Lomarsh; Anton de Kom Universiteit van Suriname. Institute for Graduate Studies & Research (New Delhi : Manohar Publishers & Distributors, 2016)
Transcript of papers presented at a conference Legacy of Slavery and Indentured Labour: Past, Present, and Future, organized in June 2013 in Suriname by the Institute of Graduate Studies & Research of the Anton de Kom University of Suriname, in collaboration with a number of government and non-government organizations.
"This volume forms the fourth and final publication originating from the conference Legacy of Slavery and Indentured Labour: Past, Present and Future, which had been organized in June 2013 by the Institute of Graduate Studies and Research (IGSR) of the Anton de Kom University of Suriname"--Introduction.
Includes bibliographical references and index.
Keywords: East Indian diaspora; Muslim diaspora; Indentured servants -- Caribbean Area -- Religious aspects; Foreign workers, East Indian -- Caribbean Area -- History